Skewered cyano-bridged cobalt naphthalocyanine polymer: An electron transport engineering - Yu, Derrick Ethelbhert C. (Animo Repository, 2010)
Naphthalocyanines (Nc) are ideal molecular conductors due to their flat and fully-conjugated structures. Attachment of a central metal (Co) and dicyano (CN) axial ligands to Nc produced CN-bridged cobalt naphthalocynanine, a skewed-type polymer complex. The polymeric species enabled intra-chain electron transport through the CN bridge by which, coupled with the inter-chain π-π overlaps, produced a multi-dimensional electronic system. This molecular design has decreased the electrical resistivity by 5 orders relative to the monomeric Co(Nc) with di-axial CN complex.